2022
DOI: 10.1111/tbed.14693
|View full text |Cite
|
Sign up to set email alerts
|

The first evidence of shaking mink syndrome‐astrovirus associated encephalitis in farmed minks, China

Abstract: A novel neurological disorder, shaking mink syndrome (SMS), emerged in Denmark and Sweden in 2000. SMS has seldom been reported in China, but the causative agent has not been detected in the country. SMS outbreaks occurred in multiple provinces in 2020. A total of 44 brain samples from minks associated with SMS were collected from Heilongjiang, Liaoning and Shandong provinces of which 28 samples (63.3%) were SMS-astrovirus (SMS-AstV)-positive by reverse transcription PCR. Histopathological examination revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the current study, we identified two zoonotic events resulting from independent introductions into the human population by different animal sources: MAstV-Sp6G2, which has been circulating in marmots and MAstV-Sp6G7, which emerged from the diversification of MAstV-Sp6G5 circulating in ruminants (bovine and sheep) ( Figure 3 ). A notable takeaway from our JANE analysis is the evidence for a host jump from MAstV-Sp6G5, present in and causing neurologic disease in minks [ 11 , 12 ] and cows [ 13 ], to the resulting MAstV-Sp6G7 in humans presenting with similar symptoms. Typically, viral species require both hosts to be in close proximity to one another to promote a jumping event, yet the prolonged stability of astroviruses in different environments (aquatic and terrestrial) provides a route to new hosts without them being physically in contact [ 9 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we identified two zoonotic events resulting from independent introductions into the human population by different animal sources: MAstV-Sp6G2, which has been circulating in marmots and MAstV-Sp6G7, which emerged from the diversification of MAstV-Sp6G5 circulating in ruminants (bovine and sheep) ( Figure 3 ). A notable takeaway from our JANE analysis is the evidence for a host jump from MAstV-Sp6G5, present in and causing neurologic disease in minks [ 11 , 12 ] and cows [ 13 ], to the resulting MAstV-Sp6G7 in humans presenting with similar symptoms. Typically, viral species require both hosts to be in close proximity to one another to promote a jumping event, yet the prolonged stability of astroviruses in different environments (aquatic and terrestrial) provides a route to new hosts without them being physically in contact [ 9 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Astroviruses appear to be ubiquitous in other mammals, typically presenting with a subclinical course in older animals, but with clinical outcomes similar to that in humans in younger animals [ 3 ]. Recent studies have revealed the implications of Mamastrovirus infections for nervous system disease in three species, including mink [ 11 , 12 ], cattle [ 13 , 14 ] and humans [ 15–19 ]. These novel strains have been grouped into different clades classified as VA1/HMO-C, HMO and MLB [ 20 ], yet it remains uncertain whether they represent different mamastrovirus species or genotypes possessing altered tropism.…”
Section: Introductionmentioning
confidence: 99%
“…Infected hosts present the main clinical features of gastrointestinal diseases (GIDs). However, astrovirus infection was also reported to be associated with extra-intestinal diseases, such as hepatitis and nephritis, in various species, including duck ( 22 , 23 ), goose ( 24 ), and mink ( 25 , 26 ). In humans, besides norovirus and rotavirus infections, astrovirus is considered to be an 10% of etiological agents associated with gastroenteritis in children globally ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%